O Papel da Leptina na Regulação da Homeostasia Energética - Sousa, Mónica (2009)
As a growing number of people suffer from obesity, understanding the mechanisms bywhich various hormones and neurotransmitters have influence on energy balance hasbeen the subject of intensive research. Recent experimental studies have implicated leptinas a crucial controller of body weight. Leptin is a 167-aminoacid peptide hormone, whichis mainly produced by adipocytes, and its levels in the circulation are increased in proportionto fat mass. Circulating leptin conveys information to the hypothalamus regardingthe amount of energy stored in adipose tissue, suppressing appetite and affecting energyexpenditure.Considerable evidence shows that this hormone is also involved in the regulation ofseveral physiological processes such as reproduction, angiogenesis, immunity, hematopoiesisand bone remodelling. Leptin acts through leptin receptors that are ubiquitouslydistributed and hence explain the pleiotropic roles of leptin.In the present review, we will summarize the recent developments in the leptin field, withparticular attention to aspects related with physiological and molecular mechanismsregulating energy homeostasis, as well as their implications in the pathophysiology ofweight disorders.